One-year outcomes in a multicentre cohort study of incident rare diffuse parenchymal lung disease in children (ChILD). Issue 2 (20th November 2019) - Cunningham, Steve; Graham, Catriona; MacLean, Morag; Aurora, Paul; Ashworth, Michael; Barbato, Angelo; Calder, Alistair; Carlens, Julia; Clement, Annick; Hengst, Meike; Kammer, Birgit; Kiper, Nural; et al.
Abstract : We performed a prospective, observational, cohort study of children newly diagnosed with children's interstitial lung disease (ChILD), with structured follow-up at 4, 8, 12 weeks and 6 and 12 months. 127 children, median age 0.9 (IQR 0.3–7.9) years had dyspnoea (68%, 69/102), tachypnoea (75%, 77/103) and low oxygen saturation (SpO2 ) median 92% (IQR 88–96). Death (n=20, 16%) was the most common in those <6 months of age with SpO2 <94% and developmental/surfactant disorders. We report for the first time that ChILD survivors improved multiple clinical parameters within 8–12 weeks of diagnosis. These data can inform family discussions and support clinical trial measurements.